2001
DOI: 10.1006/dbio.2001.0366
|View full text |Cite
|
Sign up to set email alerts
|

VegT Activation of Sox17 at the Midblastula Transition Alters the Response to Nodal Signals in the Vegetal Endoderm Domain

Abstract: In Xenopus, the prospective endoderm and mesoderm are localized to discrete, adjacent domains at the beginning of gastrulation, and this is made evident by the expression of Sox17 in vegetal blastomeres and Brachyury (Xbra) in marginal blastomeres. Here, we examine the regulation of Sox17alpha expression and the role of Sox17alpha in establishing the vegetal endodermal gene expression domain. Injection of specific inhibitors of VegT or Nodal resulted in a loss of Sox17alpha expression in the gastrula. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 64 publications
4
35
0
Order By: Relevance
“…6a). This phenomenon coincides with the reports in which the repression of Xsox17 activity in endoderm cells caused to recovery of mesodermal factor (Engleka et al 2001). It was reported that HNF1b, endodermin, and HNF3a/bin endoderm cells are directly controlled by Xsox17 ).…”
Section: Xchh Is One Of Direct Targets Of Xsox17supporting
confidence: 91%
“…6a). This phenomenon coincides with the reports in which the repression of Xsox17 activity in endoderm cells caused to recovery of mesodermal factor (Engleka et al 2001). It was reported that HNF1b, endodermin, and HNF3a/bin endoderm cells are directly controlled by Xsox17 ).…”
Section: Xchh Is One Of Direct Targets Of Xsox17supporting
confidence: 91%
“…WE, whole embryo; ϪRT, minus reverse transcriptase. Henry and Melton, 1998;Clements et al, 1999;Yasuo and Lemaire, 1999;Engleka et al, 2001;Shivdasani, 2002;Stainier, 2002;Loose and Patient, 2004). It is this collection of unknown target genes that ultimately defines the early endoderm cell.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was purified from stage 11 cultured animal caps and embryos by using an RNAqueous kit (Ambion) and quantified by spectrometer. RT-PCR for EF1␣, Brachyury, and MyoD expression was performed as described (36). Data shown are representative of five independent assays.…”
Section: Methodsmentioning
confidence: 99%